Comparison of the composition of bile acids in bile of patients with adenocarcinoma of the pancreas and benign disease - Gareth Jenkins (The Journal of Steroid Biochemistry and Molecular Biology, 2017)
Bile acids have been implicated in the development of gastrointestinal malignancies. Both the specific nature of individual bile acids and their concentration appear key factors in the carcinogenic potency of bile. Using liquid chromatography mass spectrometry (LC-MS) we performed quantitative profiling of bile extracted directly from the common bile duct in 30 patients (15 patients with pancreatic cancer and 15 patients with benign disease). Separation and detection of bile acids was performed using a 1.7μm particle size reversed-phase C18 LC column at a flow rate of 200μL/min with negative electrospray ionization MS. A significant difference (p=0.018) was seen in the concentration of unconjugated cholic acid in the malignant group (0.643mmol/L) compared to the benign group (0.022mmol/L), with an overall significant difference (p=0.04) seen in the level of total unconjugated bile acids in the malignant group (1.816mmol/L) compared to the benign group (0.069mmol/L). This finding may offer the possibility of both understanding the biology of cancer development in the pancreas, as well as offering a potential diagnostic avenue to explore. However, a larger study is necessary to confirm the alterations in bile acid profiles reported here and explore factors such as diet and microbial populations on the bile acid profiles of these patient groups.